Strength and timing of motor responses mediated by rebound firing in the cerebellar nuclei after Purkinje cell activation - Witter, Laurens; Canto, Cathrin; Hoogland, Tycho M.; De Gruijl, Jornt R.; De Zeeuw, Chris I. (Frontiers in Neural Circuits, 2013)
The cerebellum refines the accuracy and timing of motor performance. How it encodes information to perform these functions is a major topic of interest. We performed whole cell and extracellular recordings of Purkinje cells (PCs) and cerebellar nuclei neurons (CNs) in vivo, while activating PCs with light in transgenic mice. We show for the first time that graded activation of PCs translates into proportional CN inhibition and induces rebound activity in CNs, which is followed by graded motor contractions timed to the cessation of the stimulus. Moreover, activation of PC ensembles led to disinhibition of climbing fiber activity, which coincided with rebound activity in CNs. Our data indicate that cessation of concerted activity in ensembles of PCs can regulate both timing and strength of movements via control of rebound activity in CNs.